Raising Islamic values tradition on the reading of Anbiya book - Arik Cahyani; Eny Kusdarini (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Indonesia is a country with a diversity of cultures, ethnicities, religions, races, and traditions. In Indonesia, there are many combinations of cultural values and religious values that are used to elevate the values of a religion. In 2010, the Sheikh Subakir Association was formed as one of the Anbiya book reading associations in Blitar. This study aimed to determine the religious values in the tradition of reading the Anbiya book in Nglegok Sub-district, Blitar Regency, East Java. This study used a qualitative research method with a descriptive approach. The data were obtained through direct observation, in-depth interviews, and data collection with documents. The interviews were conducted with the head of the group, Sheikh Subakir, several group members, the secretary of the sub[1]district, and village communities. Based on this research, it is found that there are eight values of the Anbiya book that invites humans to always do good in everyday life. The values in the contents of the Anbiya book include: faith values, Islamic values, perfection (ihsan) values, piety values, sincerity values, reliance (tawakal) values, gratitude values, and patient values. This study concluded that the reading of the Anbiya book is preserved to maintain cultural heritage and maintain Islamic values.